Food consumption knowledge and habits in a developing country: a case of Lebanon - Boustasni, N. M. (2022)
This research work investigated the Lebanese consumers’ knowledge about food fibre and their food habits according to age groups and gender. The study was conducted from January 2021 till end of March 2021. Due to the pandemic of Covid-19 and the lockdown, the questionnaire was administered randomly through social media. The survey consisted of a longitudinal study carried out on a non-probabilistic convenience sample of 258 Lebanese participants. The responses were used to undertake a quantitative, descriptive and analytical study. The questionnaires received and considered valid, were mostly from women (59.7%) and essentially living in an urban environment (78.3%). To analyse the data, basic descriptive statistics were considered on a first level. Additionally, statistical tests were also carried out (Student t test for comparisons between two groups). Finally, results and analysis were done to evaluate the importance of food knowledge among these people in addition to their eating habits and the possible gender differences. The results revealed that there are some gender inequalities (F=6.238, α= 0.0013) in terms of knowledge about food fibre, but no living environment differences were found (F=0.36, α=0.85). Additionally, consumption habits showed major differences between female and male food behaviour, especially when it comes to eating: the frequency of eating outside from home, eating fast food and consuming fruits. The value of this study focuses on the food knowledge and habits in Lebanon, specifically in a country defined by a multi-ethnical diversity and religiosity and where food habits were mainly related to social behaviour. Therefore, this study adds more knowledge about these people’s food behaviour and valuable information about specific food attitudes.